“I feel like they’re my family”: characteristics of one successful resource couple who fosters high risk teenagers - Loehr, Matthew A. (Kansas State University, 2012)
The focus of this qualitative case study was to examine the qualities and characteristics present in a successful resource family who parents high-risk teenagers. Perspectives were gathered from the resource parents, their birth children, a foster teen living in their home, and professionals that work with these resource parents. Utilizing Family Systems Theory and content analysis of the data, themes were identified as contributing to the success of this resource family. Themes identified were inclusion, communication, boundaries, humility, and a willingness to be hurt as well as positive attitude. Implications of these themes are discussed with the literature, theory, and the use of the pre-service training that resource parents are provided. A perspective was gained from both inside and outside the resource family for analysis. A discussion around implications of these findings as well as the need to explore additional areas is outlined.
Keywords: Foster care; Foster family; Resource family; Foster home; Social Work (0452)